2008
DOI: 10.1111/j.1365-3059.2008.01862.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analyses of Wheat dwarf virus isolates from different hosts reveal low genetic diversity within the wheat strain

Abstract: Wheat dwarf virus (WDV) causes disease in wheat ( Triticum aestivum ) and barley ( Hordeum vulgare ) in many parts of Europe. The host range also includes many species of the family Poaceae. WDV is only transmitted by the leafhopper Psammotettix alienus . During a five-year period (2001)(2002)(2003)(2004)(2005), grass samples were collected in central Sweden in the vicinity of fields with WDV-infected winter wheat. Screening with ELISA and PCR identified WDV in a low number of samples (8/1098) from only three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 32 publications
6
35
0
1
Order By: Relevance
“…These isolates present a high degree of identity throughout the full genome. This low level of divergence confirms the previous report about the variability of the wheat strain of WDV, regardless of their host plants [27]. Although it has been proven that the LIR is the most variable genome segment of the wheat strain [13], our wheat isolates further underscore the low diversity in this region.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These isolates present a high degree of identity throughout the full genome. This low level of divergence confirms the previous report about the variability of the wheat strain of WDV, regardless of their host plants [27]. Although it has been proven that the LIR is the most variable genome segment of the wheat strain [13], our wheat isolates further underscore the low diversity in this region.…”
Section: Discussionsupporting
confidence: 91%
“…In conclusion, the results presented in this work have shown that the Czech isolates were divided into two distinct groups: wheat and barley strains. All three restriction profiles and sequence analyses confirm that the barley strain is restricted to the barley host, but the wheat strain seems to have multiple hosts [27], and our study having detected it in both wheat and barley plants.…”
Section: Discussionsupporting
confidence: 84%
“…This aphid damages the host not only by feeding, but also by transmitting Barley yellow dwarf virus (BYDV) (Luteoviridae: Luteovirus), which is one of the most serious viral diseases of cereal crops worldwide (Stern, ; Fereres et al ., ; Jiménez‐Martínez et al ., ; Powell & Bale, ). In the last two decades, S. avenae has caused substantial economic losses by transmitting BYDV, which has reduced barley and wheat production in many countries, for example, Germany and China (Bishop & Sandvol, ; Huth, ; Wu et a1 ., ; Ramsell et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The diseases caused by WDV and Barley yellow dwarf virus (BYDV), including CYDV, have been recognized as two of the most serious viral diseases of crops (Jiménez-Martínez et al 2004), threatening barley and wheat production and causing significant economic losses throughout the world (Bishop and Sandvol 1984; Huth 2000; Wu et al 2002; Ramsell et al 2008). …”
Section: Introductionmentioning
confidence: 99%